EFFECTS OF DIATOMACEOUS EARTH ON THE PROXIMATE COMPOSITION OF STORED COWPEA VARIETY (IT96D-610K) (2019)
A stuck' was carried out to determine the effect of a raw diatomaceous earth (DE) obtained fromBularafa community in Yobe State, Nigeria on the proximate composition of stored cowpea variety (IT96D-610K). Twelve small scale prototype silos made of two different structures (wooden and galvanised mild steel (GMS)) were constructed and used in the storage of the cowpea for a 4-month period. 7000g of cowpea at 9.88% moisture content admixed withdiatomaceous earth havingtwo different particle sizes(0.075mm and 0.090mm) and three different concentrations(0.1g, 0.05g and 0g of DE/100g of cowpea)in varying combinations were loaded into each silo. The sample admixed with zero concentration of diatomaceous earth served as the control in each of the wooden and galvanised steel structures respectively. Temperature, relative humidity and moisture content within the storage structures were monitored. Proximate compositionsuch as ash, crude protein, fat, crude fibre, carbohydrate alongside moisture content were also measured.Significant differences (p<0.05) was observed between the control sample and treated samples.The values of moisture content, ash content and crude fibre increased while crude protein, fat and carbohydrate decreased with increased storage period. At the last month of storage, wooden silo recorded a higher temperature value (28.88˚C) compared to the galvanised steel (GMS) silo which showed (22.30˚C). An increase in moisture content was observed in both silos with wooden silos showing a higher percentage rise in both control and treated samples. At the end of the fourth month the average moisture content, ash content, crude protein, fat, crude fibre and carbohydrate content of control and treated samples were(10.57% and 13.39%), (4.12% and 4.16%), (22.75% and 22.69%),(1.95% and 1.90%),(2.21% and 2.23%) and (57.75% and 55.63%) in the GMS and wooden silos respectively.Cowpea admixed with diatomaceous earth stored in GMS silo showed the best nutritional quality. Hence of all the storage materials, storage time, particle size and concentration of DE used galvanised mild steel (GMS), 0.075mm particle size and 0.05g of DE/100g of cowpea for the first four weeks of storage were seen to be the best. These proved to be the best method of storage for cowpea as the procedure retained its proximate composition. The increased crude fibre level in the treated samples is a major indicator for good health